Impact of including distillers' dried grains with solubles at expense of soybean meal on Boer influenced goat growth performance - Paine, Jason M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The objective of this project was to evaluate the efficacy of distillers' dried grains (DDGS) as a replacement of soybean meal (SBM) in a Boer-influenced goats growing ration Because diets were isonitrogenous and isocaloric, it was hypothesized that the replacement of SBM with DDGS would reduce diet costs without impacting growth performance. To test this hypothesis, forty-eight Boer-influenced goats (28.2 ± 0.96 kg BW; approximately 90 d of age) were allocated to 4 treatments in a completely random design in a climate-controlled (13° C) facility of the Kansas State University Sheep and Meat Goat Center. Goats were stratified by BW into 16 pens (4 pens/treatment; 3 goats/pen) for a 42 d finishing study. The main effect was concentration of DDGS (0, 10, 20, or 30% DM basis) which resulted in dietary treatments of 1) 0% SBM replaced by DDGS (0DDGS); 2) 33% SBM replaced by DDGS (10DDGS); 3) 66% SBM replaced by DDGS (20DDGS); and 4) 100% SBM replaced by DDGS (30DDGS). Goats remained on a self-feeder with continuous access to their respective pelleted, complete dietary treatments and clean, fresh water. Two-day weights were taken at the beginning and end of the trial, with BW, ADG, ADFI, and G:F measured and calculated every 7 d. Beginning BW were similar across all treatments (P = 0.99). The inclusion of DDGS had no effect on BW or ADFI from d 0 to d 42 (P ≥ 0.15). Both ADG (P = 0.04) and G:F (P = 0.001) increased linearly with increasing DDGS inclusion, with goats fed diets containing DDGS having 33% greater ADG (P = 0.05) than those fed diets without DDGS. Ultimately, these results confirm the hypothesis that DDGS can be used to replace SBM in the diet. At current commodity prices, this leads to a 17% savings in diet cost. This novel research shows similar improved performance measures to lambs and cattle when feeding DDGS.
Keywords: Spring 2018